3D MICROWAVE ANTENNA SYNTHESIS TAKING INTO ACCOUNT DIELECTRIC COATING AND THE DESIRED RADIATION PATTERN - O. Sh. Dautov; Ibrahim Salem (European Scientific Journal, ESJ, 2014)
The problems of microwave antenna synthesis with a dielectriccoatings, which use the desired radiation pattern characteristics as inputinformation, are very important. Based on the method of auxiliary sourcesand integro-functional equations, a solution of the three-dimensional directand inverse problems for excitation of microwave antenna array, whichconsists of a few slot emitters under a finite-size dielectric layer, isintroduced. The results of research for the antennas radiation pattern with agiven the distribution of the sources and synthesis of the amplitude and phasevoltage distribution for the slot antenna array according to the desiredradiation pattern are discussed.